Biochemical and structural characterization of cross-linked enzyme aggregates (CLEAs) of organic solvent tolerant protease - Mohd Razib, Muhammad Syafiq; Raja Abdul Rahman, Raja Noor Zaliha; Mohd Shariff, Fairolniza; Mohamad Ali, Mohd Shukuri (MDPI, 2020)
Cross-linked enzyme aggregates (CLEAs) is an immobilization technique that can be used to customize enzymes under an optimized condition. Structural analysis on any enzyme treated with a CLEA remains elusive and has been less explored. In the present work, a method for preparing an organic solvent tolerant protease using a CLEA is disclosed and optimized for better biochemical properties, followed by an analysis of the structure of this CLEA-treated protease. The said organic solvent tolerant protease is a metalloprotease known as elastase strain K in which activity of the metalloprotease is measured by a biochemical interaction with azocasein. Results showed that when a glutaraldehyde of 0.02% (v/v) was used under a 2 h treatment, the amount of recovered activity in CLEA-elastase was highest. The recovered activity of CLEA-elastase and CLEA-elastase-SB (which was a CLEA co-aggregated with starch and bovine serum albumin (BSA)) were at an approximate 60% and 80%, respectively. The CLEA immobilization of elastase strain K allowed the stability of the enzyme to be enhanced at high temperature and at a broader pH. Both CLEA-elastase and CLEA-elastase-SB end-products were able to maintain up to 67% enzyme activity at 60 °C and exhibiting an enhanced stability within pH 5–9 with up to 90% recovering activity. By implementing a CLEA on the organic solvent tolerant protease, the characteristics of the organic solvent tolerant were preserved and enhanced with the presence of 25% (v/v) acetonitrile, ethanol, and benzene at 165%, 173%, and 153% relative activity. Structural analysis through SEM and dynamic light scattering (DLS) showed that CLEA-elastase had a random aggregate morphology with an average diameter of 1497 nm.